Comparative Antibacterial Activity of Garlic (Allium sativum) Extracts and Conventional Antibiotics Against Escherichia coli Serotypes - Bufrag, Somia; Bentaher, Elham (AlQalam Journal of Medical and Applied Sciences, 2026)
The increasing prevalence of antibiotic-resistant Escherichia coli has prompted the search for alternative antimicrobial agents. This study evaluated the in vitro antibacterial activity of aqueous and ethanol extracts of garlic (Allium sativum) against four E. coli serotypes (O26, O111, O114, and O119) using the well diffusion method. Garlic extracts at concentrations ranging from 25% to 95% were compared with ten commonly used antibiotics. The results demonstrated a concentration-dependent antibacterial effect, with the 95% garlic extract producing inhibition zones of up to 30 mm, comparable to those observed for ceftriaxone and aztreonam. Several E. coli isolates exhibited resistance to lincomycin, neomycin, rifampicin, and cotrimoxazole. These findings indicate that garlic extract possesses significant antibacterial activity and may represent a promising natural alternative or adjunct to conventional antibiotics in the management of E. coli infections.